Effect of deficit irrigation on vine performance and grape composition of Vitis vinifera L. cv. Muscat of Alexandria. (17th April 2017) - Buesa, I.; Pérez, D.; Castel, J.; Intrigliolo, D.S.; Castel, J.R.
Abstract: Background and Aims: Previous research has investigated widely the effects of irrigation application in red winegrape cultivars; however, white grape cultivars have been the subject of a lesser number of field trials. An experiment was undertaken for three seasons in a drip‐irrigated, cv. Muscat of Alexandria/161‐49C vineyard to define the most sustainable irrigation strategy for white winegrapes in eastern Spain. Methods and Results: The treatments were as follows: (i) Control, irrigated at 100% of estimated crop evapotranspiration (ETc ) for the entire season; (ii) sustained deficit irrigation (SDI), irrigated at 50% of Control; (iii) early deficit (ED), where pre‐veraison irrigation was withheld, followed by 100% ETc ; and (iv) late deficit (LD), irrigated as for the Control until veraison and thereafter at 25% ETc until harvest. Yield in ED and LD was reduced 25 and 15%, respectively, compared with that of Control. Yield under SDI did not differ significantly from that of the Control and was similar to that of the ED and LD treatments. All the deficit irrigation treatments had some carry‐over effects because of a significant decrease in shoot fruitfulness and in bunch mass due to smaller berries. The ED treatment, however, led to a greater reduction in berry growth compared with that of LD. Full irrigation increased pruning mass and leaf area mainly due to larger secondary shoots, and besides delayed grape ripening. Conclusions: The SDI treatment resulted in the greatest water use efficiency, ensuring the high yield potential of the cultivar, providing that a threshold value of water stress integral of 35 MPa day during the periods from anthesis to veraison and from veraison to harvest was not surpassed. In addition, it favoured an improved grape composition, particularly in terms of grape sugar accumulation. Significance of the Study: Sustained deficit irrigation at 50% of ETc should be applied where water is scarce or expensive, paying attention to possible carry‐over effects if water withholding has to be continued for more than three seasons.